FRI0279 High prevalence of anti-CD 74 antibodies with specificity for the class II-associated invariant chain peptide (clip) in patients with axial spondyloarthritis but not in controls. (23rd January 2014) - Baraliakos, X.; Baerleken, N.; Heldmann, F.; Witte, T.; Braun, J.
Abstract : Background: The pathogenesis of axial spondyloarthritis (axSpA) including ankylosing spondylitis (AS), although known to be strongly associated with genes such as the human leukocyte antigen (HLA) B27, is still largely unclear. The extracellular part of the HLA class II g-chain (CD74) contains a class II-associated invariant chain peptide (CLIP). The ligation of CLIP by monoclonal antibodies may leadto activation of target cells and production of proinflammatory cytokines such as TNFa. Thus, anti-CD74 antibodies may play a role in the pathogenesis of axSpA. Objectives: To study the prevalence of IgG antibodies against CLIP in patients with axSpA in comparison to controls. Methods: Sera of patients with axSpA (mostly AS fulfilling the NY criteria) and non-axSpA patients were analysed for the occurrence of IgG antibodies against CD74 using an ELISA with specificity for the synthetic peptide Class II-associated invariant chain peptide (CLIP), developed by the medical university of Hannover in cooperation with AESKU Diagnostics (Wendelsheim, Germany), as recently described. A cut-off of ≥4 standard deviations of arbitrary units (AU) from the mean serum level of autoantibodies was used to qualitatively differentiate between positive and negative results. The collaborators in the laboratory (NB and TW) were blinded to the clinical diagnosis of the patients. The study was approved by the local ethical committee of the medical university of Hannover, Germany (approval number 1315-2012). Results: Overall, sera from 95 patients with axSpA and of 47 patients with other diseases (13 with rheumatoid arthritis, 17 with fibromyalgia and degenerative spinal disease each, 2 with psoriatic arthritis without axial involvement, and 3 with polymyalgia rheumatic) were collected. In the axSpA group there were 87/95 (91.6%) AS patients, 76/95 (80%) male, mean age 44±11.6 years, 80% HLA B27-positive, mean BASDAI 6.4±1.4. In the non-axSpA group there were 13/48 (27%) male patients, mean age 58.2±14.3 years. Overall, 82/95 axSpA patients (86.3%) but only 2/47 non-axSpA patients (4.3%) were positive for anti-CLIP antibodies (p≤0.0001) and significantly higher levels of anti-CLIP antibodies were detected in patients with axSpA (mean 14.3 AU) as compared to non-axSpA (0.3 AU), p≤0.0001. There were no correlations of the levels of anti-CLIP to any clinical parameters or demographics of the patients in the groups. In the axSpA group there was a tendency for more anti-CLIP positive male patients (68/76, 89.5%) vs. female patients (14/19, 73.7%, p=0.075) and for higher anti-CLIP AU in male vs. female patients (14.9 vs 11.9, p=0.058). The sensitivity of the test for a diagnosis of axial SpA was calculated as 86.2%, while the specificity was 93.7%. Conclusions: Antibodies against CD74 with specificity for CLIP were significantly associated with the diagnosis of axial SpA. Based on the good sensitivity and excellent specificity of the test, we propose that it should be evaluated in a larger patient population, also in patients with early and non-radiographic disease stages, and in primary care. Disclosure of Interest: X. Baraliakos Grant/Research support from: Centocor Inc, USA, N. Baerleken: None Declared, F. Heldmann Grant/Research support from: Centocor Inc, USA, T. Witte: None Declared, J. Braun: None Declared